A ciphertext-policy attribute-based encryption scheme with constant ciphertext length. (2nd July 2010) - Emura, Keita; Miyaji, Atsuko; Omote, Kazumasa; Nomura, Akito; , Masakazu Soshi
An Attribute-Based Encryption (ABE) is an encryption scheme where users with some attributes can decrypt ciphertexts associated with these attributes. The length of the ciphertext depends on the number of attributes in previous ABE schemes. In this paper, we propose a new Ciphertext-Policy Attribute-Based Encryption (CP-ABE) with constant ciphertext length. In our scheme, the number of pairing computations is also constant. In addition, the number of additional bits required from chosen plaintext attack-secure CP-ABE to chosen ciphertext attack-secure CP-ABE is reduced by 90% with respect to that of the previous scheme.